A comparative study of endoscopic cartilage myringoplasty used to treat wet and dry ears with mucosal-type chronic otitis media. Issue 9 (5th September 2020) - Lou, Z; Li, X
Abstract: Objective: The outcomes of dry and wet ears were compared following endoscopic cartilage myringoplasty performed to treat chronic tympanic membrane perforations in patients with mucosal chronic otitis media. Methods: Patients with chronic perforations, and with mucosal chronic otitis media with or without discharge, were recruited; all underwent endoscopic cartilage myringoplasty. The graft success rate and hearing gain were evaluated at six months post-operatively. Results: The graft success rates were 85.9 per cent (67 out of 78) in dry ears and 86.2 per cent (25 out of 29) in wet ears; the difference was not significant ( p = 0.583). Among the 29 wet ears, the graft success rates were 100 per cent in 11 ears with mucoid discharge and 77.8 per cent in the 18 patients with mucopurulent otorrhoea. Conclusion: The wet or dry status of ears in patients with chronic perforations with mucosal chronic otitis media did not affect graft success rate or hearing gain after endoscopic cartilage myringoplasty. However, ears with mucopurulent discharge were associated with increased failure rates and graft collapse, whereas ears with mucoid discharge were associated with higher graft success rates.